2006
DOI: 10.1002/cphc.200600034
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Pair Formation in the Ionic Liquid 1‐Ethyl‐3‐methylimidazolium Bis(triflyl)imide as a Function of Temperature and Concentration

Abstract: The structures and ion-pair formation in the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide are studied by a combination of FTIR measurements and DFT calculations. We could clearly distinguish imidazolium cations that are completely H-bonded to anions from those that are single H-bonded in ion pairs. Ion-pair formation already occurs in the neat IL and rises with temperature. Ion-pair formation is strongly promoted by dilution of the IL in chloroform. In these weakly polar envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
322
5
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(358 citation statements)
references
References 41 publications
23
322
5
8
Order By: Relevance
“…The FTIR spectra in the CH-stretching region could be deconvoluted into four bands. Two bands could be assigned to C(2)H and the other two to C(4)H/C(5)H. [21] Taking the averages of these pairs of bands we can predict proton chemical shifts of about 8.58 and 7.46 ppm, which is in good agreement with the measured values of about 8.57 and 7.39 ppm, respectively. [4,5] (see Table 1 and the arrows in Figure 5) The relations can also be used for ILs that are less polar and more hydrophobic, and they are always valid-independently of the specific nature and the interactions of the ILs-because all the spectroscopic properties reflect the same chemical environment in one IL.…”
Section: Mim]a C H T U N G T R E N N U N G [Scn] and [C 2 Mim]a C H Tsupporting
confidence: 82%
See 1 more Smart Citation
“…The FTIR spectra in the CH-stretching region could be deconvoluted into four bands. Two bands could be assigned to C(2)H and the other two to C(4)H/C(5)H. [21] Taking the averages of these pairs of bands we can predict proton chemical shifts of about 8.58 and 7.46 ppm, which is in good agreement with the measured values of about 8.57 and 7.39 ppm, respectively. [4,5] (see Table 1 and the arrows in Figure 5) The relations can also be used for ILs that are less polar and more hydrophobic, and they are always valid-independently of the specific nature and the interactions of the ILs-because all the spectroscopic properties reflect the same chemical environment in one IL.…”
Section: Mim]a C H T U N G T R E N N U N G [Scn] and [C 2 Mim]a C H Tsupporting
confidence: 82%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] IR spectroscopy is applied to study the structure of ILs, in particular the strength of the interactions between anions and cations. [19][20][21] However, there is no available systematic study of the structural and dynamical properties by using NMR and IR spectroscopy. Therefore, it is still not known whether and how these properties are related to each other and what we can learn from them.…”
Section: Introductionmentioning
confidence: 99%
“…1), we were guided by the Fourier transform infrared spectroscopy (FTIR) and Raman results on liquid [EMIM]Tf2N. 21,[24][25][26][27][28][29] Accordingly, the aliphatic C-H modes of the CH2 group, the CH3 terminal group of the ethyl chain, and the CH3 group bonded to the [EMIM] ring are seen between 2850 and about 3000 cm -1 . The spectrum, in its general structure, resembles that for [BMIM]BF4, discussed in some detail in Ref.…”
Section: Assignment Of Spectral Structuresmentioning
confidence: 99%
“…The redshift of theA-H stretching vibration is often used as evidence for A-H·B hydrogen bonding, where A and B are highlyelectronegativeatoms,suchasOandN.Recentstudies have shown that if A is a carbon atom, which is attached to electronegative groups, the C-H groups may also form an energetically stable weak hydrogen bond. [21][22][23][24][25] Several studies have shown that C-H·O and C-H·X (X = F, Cl, Br) hydrogen bonds play an important role in the structure of ionic liquids, especially those derived from the 1-alkyl-3-methylimidazolium cation. 1,2,21,22 One of the intriguing aspects of weak hydrogen bondsisthattheC-Hcovalentbondtendstoshortenasaresult oftheformationofweakhydrogenbonds.…”
Section: Introductionmentioning
confidence: 99%